Genetic polymorphism of xenobiotic biotransformation genes, TNF-α and IL-4 in obstructive jaundice - A. A. Natalsky; S. V. Tarasenko; A. A. Nikiforov; O. V. Zaytsev; O. D. Peskov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study polymorphism of СYP2E1-1293 G/C (c1/c2), CYP 3А4 1А/1В, NAT2 Leu161Leu (481 c/t), GSTP1 Ile105Val, IL4 C-589T, TNF-α G-308A genes at syndrome of obstructive jaundice and uncomplicated gallstone disease.Material and methods. Overall 54 patients were divided into three comparison groups: those with obstructive jaundice of benign etiology, with cholestasis due to malignancy and uncomplicated gallstone disease. Genomic DNA of patients obtained from blood leukocytes analysed with application of «DNK-ekspresskrov» reagent utilizing «SNP-ekspress-RV» device of LLC Research and production company «Litekh» (Moscow).Results. Carriage of C allele of СYP2E1 gene is a risk factor of development of biliary diseases. The interrelation of A allele of TNF-α gene G-308A (OR=2,68, 95% CI 1,23-5,84) with high risk of obstructive jaundice due to choledocholithiasis was revealed. At the same time carriage of Т-allele of NAT2 Leu161Leu and IL4 C-589T genes reduces risk of obstructive jaundice of benign etiology.Conclusion. The high risk of biliary diseases is associated to allele C of СYP2E1-1293 G/C gene. Carriers of A allele of TNF-α gene G-308A have higher risk of obstructive jaundice on a background of gallstone disease, while Т alleles of NAT2 Leu161Leu and IL4 C-589T genes have protective action for posthepatic cholestasis.